2020
DOI: 10.4314/ajesms.v16i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perceptions towards the utilization of WhatsApp in supporting teaching and learning of chemistry during COVID-19 pandemic in Rwandan secondary schools

Abstract: This paper reports the results about teachers’ perceptions towards the utilization of WhatsApp in supporting teaching and learning of chemistry during the COVID-19 pandemic in Rwandan selected secondary schools. The collected data by using a survey questionnaire were from 18 chemistry teachers in Nyarugenge and Kicukiro Districts. The findings illustrated that WhatsApp is effective for teaching chemistry and supporting students learning. This application promotes students’ motivation, engagement, collaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…They perceived students were motivated by and interacted more in online classes. Parents and guardians were identified as potential resources to prevent student distractions (Nsabayezu et al, 2020). We found similar results in our study, which also highlighted the negative impact of parental involvement.…”
Section: Discussionsupporting
confidence: 88%
“…They perceived students were motivated by and interacted more in online classes. Parents and guardians were identified as potential resources to prevent student distractions (Nsabayezu et al, 2020). We found similar results in our study, which also highlighted the negative impact of parental involvement.…”
Section: Discussionsupporting
confidence: 88%
“…Some of the advantages of using the platform for online STEM education include quick and recursive feedback to students, easily accessible through smart devices including smartphones, user friendly and great collaboration (Violaine, 2019 ). It was found that Google classroom like other applications such as WhatsApp, and Canvas allows sharing of STEM multimedia with students from sites such as PhET and CK-12 Foundations, and YouTube which helps content retention, and motivation for autonomous learning (Nsabayezu et al, 2020 ; Violaine, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result is due to the fact that most schools lack the infrastructure to use e-learning, in addition to poor internet-connected networks, lack of equipment, and sometimes due to old school buildings not equipped for e-learning requirements. This is confirmed by the study (Nsabayezu et al, 2020) which revealed that the challenges lie in the problems of Internet connectivity including cost and lack of smartphones and computers.…”
Section: Discussionmentioning
confidence: 53%